Analysis of Long Non-Coding RNA in Cryptosporidium parvum Reveals Significant Stage-Specific Antisense Transcription - Li, Yiran; Baptista, Rodrigo P.; Sateriale, Adam; Striepen, Boris; Kissinger, Jessica C. (Frontiers in Cellular and Infection Microbiology, 2021)
Cryptosporidium is a protist parasite that has been identified as the second leading cause of moderate to severe diarrhea in children younger than two and a significant cause of mortality worldwide. Cryptosporidium has a complex, obligate, intracellular but extra cytoplasmic lifecycle in a single host. How genes are regulated in this parasite remains largely unknown. Long non-coding RNAs (lncRNAs) play critical regulatory roles, including gene expression across a broad range of organisms. Cryptosporidium lncRNAs have been reported to enter the host cell nucleus and affect the host response. However, no systematic study of lncRNAs in Cryptosporidium has been conducted to identify additional lncRNAs. In this study, we analyzed a C. parvum in vitro strand-specific RNA-seq developmental time series covering both asexual and sexual stages to identify lncRNAs associated with parasite development. In total, we identified 396 novel lncRNAs, mostly antisense, with 86% being differentially expressed. Surprisingly, nearly 10% of annotated mRNAs have an antisense transcript. lncRNAs occur most often at the 3′ end of their corresponding sense mRNA. Putative lncRNA regulatory regions were identified and many appear to encode bidirectional promoters. A positive correlation between lncRNA and upstream mRNA expression was observed. Evolutionary conservation and expression of lncRNA candidates was observed between C. parvum, C. hominis and C. baileyi. Ten C. parvum protein-encoding genes with antisense transcripts have P. falciparum orthologs that also have antisense transcripts. Three C. parvum lncRNAs with exceptional properties (e.g., intron splicing) were experimentally validated using RT-PCR and RT-qPCR. This initial characterization of the C. parvum non-coding transcriptome facilitates further investigations into the roles of lncRNAs in parasite development and host-pathogen interactions.